Temperature dependences of air-broadening, air-narrowing and line-mixing coefficients of the methane ν3 R(6) manifold lines: application to in-situ measurements of atmospheric methane - Ghysels-Dubois, Mélanie; Gomez, L.; Cousin, J.; Tran, H.; Amarouche, N.; Engel, A.; Levin, Ingeborg; Durry, G. (Journal of quantitative spectroscopy & radiative transfer, 2014)
In this work, we have revisited the spectroscopy of the R(6) manifold of the ν3 band of methane which is particularly suitable for in situ laser monitoring of CH4. For that purpose, a home-made Difference Frequency Generation (DFG) laser emitting at 3.24µm has been coupled to a cryogenically-cooled optical cell to investigate the temperature dependences of the air-broadening, the air-narrowing and the air-mixing coefficients of these ν3 R(6) manifold transitions. The temperatures of the measurements range from 213.5K to room temperature. These are typically the temperatures found in the troposphere and the lower stratosphere. Finally, the measured spectroscopic parameters have been used to process the in-situ methane absorption spectra recorded by a balloon-borne laser diode spectrometer.